Proposed European Competence Network on Mastocytosis-American Initiative in Mast Cell Diseases (ECNM-AIM) response criteria in advanced systemic mastocytosis - Gotlib, Jason; Schwaab, Juliana; Shomali, William; George, Tracy I.; Radia, Deepti H.; Castells, Mariana; Carter, Melody C.; Hartmann, Karin; Álvarez-Twose, Ivan; Brockow, Knut; Bonadonna, Patrizia; Hermine, Olivier; et al. (The journal of allergy and clinical immunology. In practice, 2022)
Advanced systemic mastocytosis (AdvSM) is characterized by the presence of KIT D816V and other somatic mutations (eg, in SRSF2, ASXL1, and RUNX1) in 95% and 60% to 70% of patients, respectively. The biological and clinical consequences of AdvSM include multilineage involvement (eg, associated hematologic neoplasm) in 60% to 80% of patients, variable infiltration and damage (C-findings) of predominantly bone marrow and visceral organs through affected mast cell (MC) and non-MC lineages, and elevated levels of serum tryptase. Recently, the treatment landscape has substantially changed with the introduction of the multikinase/KIT inhibitor midostaurin and the selective KIT D816V inhibitor avapritinib. In this review, we discuss the evolution of AdvSM response criteria that have been developed to better capture clinical benefit (eg, improved responses and progression-free and overall survival). We propose refined response criteria from European Competence Network on Mastocytosis and American Initiative in Mast Cell Diseases investigators that use a tiered approach to segregate the effects of histopathologic (eg, bone marrow MC burden, tryptase), molecular (eg, KIT D816V variant allele frequency), clinical (eg, C-findings), and symptom response on long-term outcomes. These response criteria require evaluation in future prospective clinical trials of selective KIT inhibitors and other novel agents.